Professional competency training at the university through formative projects - Alonso Betancourt, Luis Aníbal; Larrea Plúa, Johnny Javier; Moya Joniaux, Carlos Augusto (Transformación, 2024)
Objective: Professional competencies training is still a current topic of research. Many important scientific contributions have been provided on the matter but not all of them have combined instructional, educational and developmental dimensions. Hence, this article is intended to experimental evaluation, of a methodology for professional competency training at the university, based on designing, developing and evaluating formative projects. Methods: The analysis of documents was used for the construction of a theoretical framework, the systemic approach was used for devising the methodology, and statistical tests were given to verify its reliability. Results: The methodology main finding is a methodology for professional competency training of Mechanic Engineering Major students at the University of Holguin in Cuba. Encouraging results are evidenced in the selected sample, as well as enterprises hosting students’ the formative projects. Conclusions: The experiment corroborates that that the training of professional competencies demands the application of a methodology based on formative projects integrating academic, practical practice, and researching components on an innovative basis under the direction of the instructional, educational and developmental dimensions as well as learning through problem-solving methods. The methodology use seems to be suitable for engineering majors at Cuban and foreign universities.